Breaking Taboo: Explaining the United Arab Emirates’ Decision to Establish Diplomatic Relationship with Israel - Broto Wardoyo; Rizal Valentino (Global Strategis, 2022)
Uni Emirat Arab (UEA) membuka hubungan diplomatik dengan Israel, yang bertentangan dengan Inisiatif Perdamaian Arab (IPA) yang juga ditandatangani oleh UEA, yang menyatakan agar tidak membuka hubungan diplomatik dengan Israel sebelum Palestina mendapatkan kemerdekaan. Selama ini, ancaman dari Iran ini ditangkal oleh eksistensi Amerika Serikat (AS) di kawasan Timur Tengah, namun seiring dengan berkurangnya perhatian AS pada kawasan Timur Tengah maka muncul kebutuhan untuk membangun aliansi dengan like-minded countries yang memiliki persepsi ancaman yang sama. Tulisan ini akan menjelaskan lebih dalam mengenai justifkasi UEA untuk tetap membuka hubungan diplomatik dengan Israel terlepas dari komitmen mereka terhadap IPA, melalui argumen bahwa keputusan UEA didorong oleh adanya persepsi akan ancaman dari Iran terhadap budaya stratejik mereka, dan lebih lanjut berkontribusi pada kajian mengenai faktor kultural dalam perumusan kebijakan luar negeri suatu negara. United Arab Emirate (UAE) is normalizing its diplomatic relationship with Israel, conﬂicting with the Arab Peace Initiative of which the UAE is one of the signatories, which stated that no Arab states should normalize diplomatic relationship with Israel before the Palestinians regain their rights to independence. Prior to UAE’s recent decision, the United States’ presence in Middle East has been the deterrence to the threat from Iran and now that US’ attention for the region has declined, the UAE needs partner from like-minded countries to secure its foothold against Iranian threat. This article will further explain the UAE’s decision to break the taboo in normalizing their diplomaticrelationship with Israel, by arguing that the UAE’s perception of threat from Iran, deeply embedded in UAE’s strategic culture, has led to the decision to normalize diplomatic relationship with Israel, and oﬀers a cultural insight of a foreign policy decision making process in the study of foreign policy analysis.